Himalayan soap pod tree (Gymnocladus assamicus) : an ecologically and economically important tree on the brink of extinction /: an ecologically and economically important tree on the brink of extinction. ([2020]) - Choudhury, Baharul Islam; Khan, M. L
No abstract available